The phase of the de Haas–van Alphen oscillations, the Berry phase, and band-contact lines in metals - Mikitik, G.P.; Sharlai, Yu.V. (Физика низких температур, 2007)
We point out that measurements of a phase of the de Haas–van Alphen oscillations can give information on a degeneracy of electron-energy bands in a metal even though this degeneracy occurs far away from its Fermi level. As an illustration of this statement, the published experimental data on the de Haas–van Alphen effect in LaRhIn₅, graphite, and zinc are discussed.